Evaluation of Hybrid III and THOR-M neck kinetics and injury risk under various restraint conditions during full-scale frontal sled tests. (21st March 2018) - Albert, Devon L.; Beeman, Stephanie M.; Kemper, Andrew R.
Abstract: Objective: The objective of this research was to compare the kinetics and predicted injury risks of the Hybrid III (HIII) and Test device for Human Occupant Restraint (THOR)-M necks during full-scale frontal sled tests under 3 safety restraint conditions: knee bolster (KB), knee bolster and steering wheel airbag (KB/SWAB), and knee bolster airbag and steering wheel airbag (KBAB/SWAB). Methods: Twelve sled tests were performed for the HIII and THOR-M, and 8 matched sled tests were performed using postmortem human surrogates (PMHSs). The tests were designed to match the 2012 Toyota Camry New Car Assessment Program (NCAP) full-scale crash test. Upper and lower neck forces and moments were collected from the HIII and THOR-M load cells. Inverse dynamics was used to calculate PMHS upper neck forces and moments from acceleration data until the time of head contact. The PMHSs experienced head contact with the SWAB before appreciable neck loading occurred. Therefore, PMHS neck forces and moments were only compared to the HIII and THOR-M for the KB condition. Neck injury risks were calculated for the HIII and THOR-M and were compared to the injuries observed for the PMHSs. Results: The HIII had greater upper and lower neck shear forces than the THOR-M, whereas both surrogates had similar upper and lower neck axial forces. The HIII also experienced greater peak upper neck bending moments than the THOR-M, which experienced negligible upper neck bending moments. Before head contact, the PMHSs experienced upper neck flexion, and the HIII experienced extension. The HIII and THOR-M injury risk curves predicted less than a 50% risk of an Abbreviated Injury Scale (AIS) 3+ injury. No AIS 3+ neck injuries were observed for the PMHS tests, but at least one AIS 2 injury was observed per condition. Conclusions: The results of this study showed that the HIII and THOR-M had different neck kinetics for these restraint conditions. In particular, the THOR-M experienced lower upper neck shear forces and bending moments. These differences are likely due to the very different neck designs of the anthropomorphic test dummies (ATDs), particularly the increased compliance of the THOR-M neck. Despite these differences, both ATDs still predicted a similar risk of AIS 3+ neck injury.